LARANGAN PENYEDIAAN TEMPAT BAGI PENJUAL BARANG HASIL PELANGGARAN HAK CIPTA DIBUAT UNTUK MEWUJUDKAN NILAI KEADILAN - TRI MINARTI, SH A.2021141017, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2017)
ABSTRACTPROHIBITION OF SELLER FOR PROVIDING THE RESULTS OF COPYRIGHT INFRINGEMENT IS MADE TO REALIZE VALUE OF JUSTICEOne function of the law is to bring about justice therefore interested in testing the true authors of this provision was made to bring justice to the author / copyright holder. This thesis aims to analyze the value of justice in the prohibition provision for sellers Copyright infringing goods.This research in the realm of normative research. The research data obtained by studying Ref material, which then systemizationand then analyzed, to the conclusions to be drawn.The results showed that provision Article 10 UUHC No. 28 of 2014 on the prohibition of the managers of trading places forbidden to let sales / doubling goods resulting from infringement of copyright and / or related rights in a trade under its management are intended to be able to realize the values of justice, especially for the author / copyright holder and as an effort to secure the economic rights creator and / or copyright holder.Keywords: Business premises, Copyright Infringement, Justice Values2ABSTRAKLARANGAN PENYEDIAAN TEMPAT BAGI PENJUAL BARANG HASIL PELANGGARAN HAK CIPTA DIBUAT UNTUK MEWUJUDKAN NILAI KEADILANSalah satu fungsi hukum adalah untuk mewujudkan keadilan oleh sebab itu penulis tertarik untuk menguji benarkah ketentuan ini dibuat untuk mewujudkan keadilan bagi para pencipta/pemegang hak cipta.Tesis ini bertujuan untuk menganalisis nilai keadilan dalam ketentuan larangan penyediaan tempat bagi penjual barang hasil pelanggaran Hak Cipta.Penelitian ini masuk dalam ranah penelitiab normative. Data penelitian diperoleh dengan cara mempelajari bahan pustka, yang kemudian disistimatisasi dan selanjutnya dianalisis, hingga dihasilkan kesimpulan.Hasil penelitian menunjukan bahwa ketentuan Pasal 10 UUHC No. 28 Tahun 2014 tentang larangan para pengelola tempat perdagangan dilarang membiarkan penjualan/penggandaan barang hasil pelanggaran hak cipta dan/atau hak terkait di tempat perdagangan yang dikelolanya dimaksudkan agar dapat mewujudkan nilai keadilan terutama bagi para pencipta/pemegang hak cipta dan sebagai upaya menjamin diperolehnya hak ekonomi pencipta dan/atau pemegang hak cipta.Kata Kunci :Pengelola tempat, Pelanggaran Hak Cipta, Nilai Keadilan